The Functions of Visual Representational Meaning in Supporting the Ideational Meaning in Cambridge Guess What Pupil’s Book - Rabbani, Syarifatusnain Maulida Wahyu; Saleh, Mursid; Sutopo, Djoko (English Education Journal, 2021)
In a learning context, students are usually faced with images and texts, especially in textbooks they carry around with them. Nowadays, meaning-making rarely depends on language alone. Sometimes, the combination between image, color, sound, and action symbol have been considered as paralanguage no longer play a subordinate role in modern communication. This research aims to explain 1) the existence of visual representational meaning and the text ideational meaning in Cambridge Guess What Pupil’s Book 6, 2) the function of visual representational meaning and the text ideational meaning in the Cambridge Guess What Pupil’s Book 6, and 3) the function of visual representational meaning and the purposes of the texts in Cambridge Guess What Pupil’s Book 6. The findings showed the existences of the visual representational meaning and the ideational meaning of the texts. They had the same participants and processes. However, not all clauses on the texts had the same participants. There were only several clauses that had the same participants with the figures. It meant visual representational meaning only could visualize the description of the same participants or visualize the narration of the same processes.